Prevalence of diabetes and diabetic macular edema in patients undergoing senile cataract surgery in Italy: The DIabetes and CATaract study. Issue 2 (March 2020) - Panozzo, Giacomo; Staurenghi, Giovanni; Dalla Mura, Giulia; Giannarelli, Diana; Alessio, Giovanni; Alongi, Salvatore; Appolloni, Romolo; Baldascino, Antonio; Boscia, Francesco; Caporossi, Aldo; Cereda, Matteo; D'Ugo, Erminia; et al.
Background: The purpose of this study is to determine the prevalence of diabetes and diabetic macular edema in patients undergoing senile cataract surgery in Italy. Methods: It is a prospective, multicenter, cross-sectional study. Thirteen ophthalmic units equally distributed across the Italian territory have been involved in the study. For a period of 3 months, all subjects undergoing phacoemulsification received an Optical Coherence Tompgraphy (OCT) scan and were screened for the anamnestic presence of diabetes. In addition, five selected units collected blood samples from all their patients to measure glycated hemoglobin (HbA1c) levels and detect the presence of occult diabetes (HbA1c > 6.5%). In diabetic patients, levels of retinopathy were measured and diabetic macular edema was considered significant (clinically significant macular edema) when foveal thickness was above 30% of normal levels. Results: A total number of 3657 subjects have been screened. Among them, 20.4% were diabetics. Prevalence of diabetes was significantly higher in males (24.7%) than in females (17%). Levels of HbA1c were tested in a representative sample of 1216 consecutive subjects, and occult diabetes was diagnosed in 4.8% of cases. No significant differences were observed between age groups or different geographic areas. Among diabetic patients, diabetic macular edema of any kind was present in 27.5% (clinically significant macular edema (6.6%)). No significant differences were seen in the prevalence of diabetic macular edema between males and females or between age groups. Among the 745 diabetic patients, no signs of retinopathy were seen in 537 subjects (76.3%), while 101 patients (14.3%) had nonproliferative retinopathy, 13 (1.7%) had nontreated proliferative diabetic retinopathy, and 53 (7.5%) had laser-treated retinopathy. In the entire sample of 3657 subjects, a normal macula was present in 90.9% of cases, diabetic macular edema of any kind in 5.4%, and other maculopathies in 3.4%. Conclusion: In this large cohort study on patients undergoing cataract surgery, more than one-fourth were diabetics and more than one-fourth of these had diabetic macular edema. These high prevalences suggest the opportunity to plan an adequate preoperative assessment in all patients in order to reduce the risk of postoperative development or worsening of a sight-threatening complication such as chronic diabetic macular edema.